The official opening of UMP main campus and naming of Tun Abdul Razak Chancellery by PM - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) main campus in Kuala Pahang here was officially opened by Prime Minister, Dato’ Sri Mohd Najib Tun Abdul Razak on February 21, 2016.